Validity of the positive and negative affect schedule (PANAS) in children - González Arratia López Fuentes, Norma Ivonne (2015)
The present study aims to evaluate the psychometric properties of the Positive and Negative Affect Schedule (PANAS), its convergent validity with a measure of resilience and reliability in a sample of 194 children of both sexes, between 9 and 12 years old in Toluca city, Mexico. The exploratory factor analysis with the principal components method and orthogonal rotation, verifies the dimensional structure that explains 44.85 % of the total variance, and high Cronbach Alpha reliability, suggesting psychometric characteristics similar to those of the original version, and confirms the convergent validity with resilience. It is concluded that the scale is relevant to Mexican children, but there is a need to expand the sample to allow the use of confirmatory techniques.